The Physiological Basis of Improved Heat Tolerance in Selected Emmer-Derived Hexaploid Wheat Genotypes - Ullah, Smi; Trethowan, Richard; Bramley, Helen (Frontiers in Plant Science, 2021)
Wheat is sensitive to high temperature stress with crop development significantly impaired depending on the severity and timing of stress. Emmer wheat is a first domesticated wheat with considerable variation for stress tolerance. Various physiological mechanisms have been identified as selection targets; however, the complex nature of the trait and high genotype x temperature interaction limits the selection process. One hundred and eighty-five emmer-based hexaploid lines were evaluated in the field for two consecutive years using a time-of-sowing strategy to classify the material as tolerant or susceptible to heat stress. A contrasting pair of emmer-based hexaploid lines (classified as tolerant; G1 and susceptible; G2) developed from a backcross to the same recurrent hexaploid parent was chosen based on heat stress response in the field and evaluated under controlled glasshouse conditions. The same pair of contrasting genotypes were also subsequently exposed to a short period of elevated temperature (4 days) at anthesis under field conditions using in-field temperature-controlled chambers to determine genotype response to intervallic heat stress. The greenhouse and field-based heat chambers produced comparable results. G1 was consistently better adapted to both extended and short periods of heat stress through slow leaf senescence under heat stress, which extended the grain filling period, increased photosynthetic capacity, increased grain filling rates and resulted in greater kernel weight and higher yield. Slow leaf senescence was an important trait that stabilised grain yield under heat stress. The combination of phenotyping methods was effective in identifying heat tolerant materials and their associated traits.